Recreational resources of East Kazakhstan as a basis for tourism sphere developm (Journal of Geography and Environmental Management, 2018)
Comprehensive analysis of fund resources of the Department of Tourismand Markakol and West-Altai state nature reserves has been completed.Main problems of the tourism industry have been identified. Quantitativeand qualitative values of recreational potential have been determinedfor the main areas of the analyzed territory in different nature complexesto correct and address the problems.Field study results have confirmedthat recreational opportunities of nature and tourist destinationsof EastKazakhstan region are viable. Health tourism cluster development modelhas been developed for the region based on the modeling and excursiontechniques. Science Department of Markakol and West Altai state naturereserves has suggested an eco path guided tours.